2009
DOI: 10.1007/s12282-009-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of neoadjuvant treatment with doxorubicin, docetaxel, and capecitabine (ATX) in locally advanced or inflammatory breast cancer

Abstract: ATX every 28 days for four cycles is associated with a modest activity (low pCR rate) in the neoadjuvant setting of LABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Comparing the taxane non-containing protocols to concomitant TE protocol in our study response rates and survival data were equivalent and analogous with results of these and other [36,37] groups. We could also confirm, that achieving pCR renders a greater probability of longer PFS and LPFS, but not significant tendency in OS data.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing the taxane non-containing protocols to concomitant TE protocol in our study response rates and survival data were equivalent and analogous with results of these and other [36,37] groups. We could also confirm, that achieving pCR renders a greater probability of longer PFS and LPFS, but not significant tendency in OS data.…”
Section: Discussionsupporting
confidence: 83%
“…These advantages may include allowing patients with inoperable cancers to become candidates for surgical resection (11, 12), targeting clinically occult micro-metastases (18), and providing an opportunity to deliver cytotoxic agents to the tumor with intact native vasculature (19). Also, several studies have shown that NAC is tolerable and significantly improves outcomes compared to surgery alone in patients who had inflammatory or locally advanced breast cancer (20, 21). Since NAC tends to be offered to patients with advanced disease, perhaps our finding that NAC is a negative predictor of FPT may be related to the fact that oncologists treating women with advanced cancer defer the discussion about fertility issues when the prognosis is poor (22).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding was that NAC has a broader use under research protocols at Center-1, and a higher utilization rate at that institution, even in lower stage breast cancers. At Center-1, only 35.2 % of the patients in NAC group met the informal criteria (inoperable inflammatory or locally advanced breast cancer) for NAC use (21, 23). On the other hand, NAC was used only with advanced stage cancers at Centers 2 and 3, where only 3 patients received NAC, all of whom had stage III disease, large tumors (4-6 cm) and lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, women who received neoadjuvant chemotherapy were significantly less likely to pursue FP treatments. This finding is significant because cancer treatment plans may be modifiable and the survival gain of neoadjuvant chemotherapy in early stage breast cancer has not been validated [18]. This reinforces the importance of inter-professional collaboration to coordinate medical and FP treatments to appropriately maximize a patient's opportunity for future fertility.…”
Section: Limitations Of Current Fp Programmentioning
confidence: 99%